Novel manufacturing process of pneumococcal capsular polysaccharides using advanced sterilization methods - Yuelong Li; Xin Cao; Xueting Huang; Yanli Liu; Jianlong Wang; Qian Jin; Jiankai Liu; Jing-Ren Zhang; Haifa Zheng (Frontiers in Bioengineering and Biotechnology, 2024)
Pneumococcal disease is caused by Streptococcus pneumoniae, including pneumonia, meningitis and sepsis. Capsular polysaccharides (CPSs) have been shown as effective antigens to stimulate protective immunity against pneumococcal disease. A major step in the production of pneumococcal vaccines is to prepare CPSs that meet strict quality standards in immunogenicity and safety. The major impurities come from bacterial proteins, nucleic acids and cell wall polysaccharides. Traditionally, the impurity level of refined CPSs is reduced by optimization of purification process. In this study, we investigated new aeration strategy and advanced sterilization methods by formaldehyde or β-propiolactone (BPL) to increase the amount of soluble polysaccharide in fermentation supernatant and to prevent bacterial lysis during inactivation. Furthermore, we developed a simplified process for the CPS purification, which involves ultrafiltration and diafiltration, followed by acid and alcohol precipitation, and finally diafiltration and lyophilization to obtain pure polysaccharide. The CPSs prepared from formaldehyde and BPL sterilization contained significantly lower level of residual impurities compared to the refined CPSs obtained from traditional deoxycholate sterilization. Finally, we showed that this novel approach of CPS preparation can be scaled up for polysaccharide vaccine production.